Novel Wave Surfaces to the Fractional Zakharov-Kuznetsov-Benjamin-Bona-Mahony Equation - Baskonus, Haci Mehmet; Yel, Gulnur; Bulut, Hasan (Amer Inst Physics, 2017)
In this work, we apply the improved Bernoulli sub-equation function method to the space-time fractional Zakharov-Kuznetsov-Benjamin-Bona-Mahony equation. We obtain new travelling wave solutions to this model for values of M,n and m. We have obtained hyperbolic function solutions that describe some physical phenomena. Two and three-dimensional surfaces of travelling wave solutions are plotted by using Wolfram Mathematica 9. At the end of this study, a conclusion is given by mentioning important findings.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 19-25, 2016 -- Rhodes, GREECE